Simulação e reconstrução de hologramas de objetos 2D e 3D por camadas usando Python - Pereira, Pedro Miguel (Universidade Federal de São Carlos, 2026)
This work presents the development and evaluation of routines for generating and reading digital holograms using the Python programming language and the LightPipes library. The methodology involved simulating light propagation and diﬀraction—using the convolution method—for two-dimensional and layered three-dimensional objects, employing an in-line holography conﬁguration. Subsequently, the implemented routines were applied to process holograms sourced from papers on marine zooplankton. The results demonstrate that the holograms computationally generated by these routines adequately preserve information regarding the shape, transmittance, and depth of the simulated objects, allowing for high-ﬁdelity recovery. The routines’ ability to reconstruct images from holograms obtained in real experiments is also demonstrated, even when some experimental parameters are unavailable.
Simulation and reconstruction of holograms of 2D and layer-based 3D objects using Python
Keywords: Holografia; Python; Simulação; CIENCIAS EXATAS E DA TERRA::FISICA; 4. Educação de Qualidade